Adsorption of Remazol Brilliant Blue R Dye Using Activated Carbon from Emty Palm Oil Bunches - Denny Aris Setiawan; Sirajuddin; Ricky Marthin De Tulus Wanwol (JURNAL SAINS NATURAL, 2023)
Various types of dyes are used in the textile industry, including Remazol Brilliant Blue R dye. Remazol dye is a type of anthraquinone which is very difficult to remove if it is contaminated in the environment. One method of dealing with dyes that pollute the environment is adsorption using activated carbon. The material for activated carbon has the most potential to come from the palm oil industry, namely empty palm fruit bunches because they are widely available and have economic value. This study aimed to determine the effect of varying exposure time between activated carbon made from empty palm fruit bunches and textile dye Remazol Brilliant Blue R on decreasing the concentration of dye Remazol Brilliant Blue R. The adsorption process was carried out with the ratio of adsorbent mass: dye volume w/v (0.1:15) and varying the contact times of 20, 40, 60, 80, 100 and 120 minutes. The initial concentration of textile substances was 23.2121 mg/L and was contacted between Remazol Brilliant Blue R textile substances with adsorbents using a shaker. Analysis of adsorption results using a UV – Vis instrument with a wavelength of 670 nm for Remazol Brilliant Blue R dye. The results showed that the best adsorption conditions was 60 minute contact time, with a removal percentage of 87.23% with an adsorption capacity of 3.0373 mg/g. The adsorption of Remazol Brilliant Blue R follows the Langmuir adsorption equation model with an R2 of 0.9997.